Peningkatan Literasi Anak Melalui Program Gelar Baca di TBM Sabilul Faizin, Malang - Roidah, Ida Syamsu; Siti Winarsih (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
TBM is a forum for the community to learn using books as a reading source and activity programs to build community literacy awareness. Currently, people's literacy culture is increasingly low as a result of their low interest in reading. To improve literacy culture, a reading degree program was held at TBM Sabilul Faizin, Slatri Hamlet, Pait Village, Kasembon District, Malang Regency. The method used is four stages; 1) Discussion and coordination stage, 2) Planning and preparation stage, 3) Activity implementation stage, 4) Activity results evaluation stage. This reading degree program is carried out by dividing participants into two groups, namely children in the low level group and children in the high level group. Reading for low level children is done by telling stories, while for high level children it is done by reading story books. The results of this activity can increase children's reading literacy and foster a literacy culture in children at TBM Sabilul Faizin. It is hoped that this activity can be carried out in a sustainable manner.